Clustered Regularly Interspaced Short Palindromic Repeats- Associated Protein Cas9 (CRISPR/Cas9) Terenkapsulasi Nanopartikel Berbasis Hibridisasi Polimer Lipid (LPNs) sebagai Modalitas Mutakhir Terapi pada Huntington’s Disease - Re Septian Ilhamsyah; Annisa Dewi Nugrahani; Firman Kurniawan (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2018)
Introduction: Huntington’s disease (HD) is a rare neurodegenerative disease resulting in motoric, cognitive, and psychiatric dysfunction caused by CAG repeat elongation in the mutated HTT gene (mHTT). Currently, there has not been any effective and efficient curative treatment and there are only symptomatic treatments. To overcome this situation, Clustered Regularly Interspaced Short Palindromic Repeats-Associated Cas9 Protein (CRISPR/Cas9) emerges as a prospective revolutionaire biomolecular approach toward Huntington’s disease supported by Lipid Polymer Nanoparticles (LPNs) vector with excellent features as a vector that deliver CRISPR Cas9 to the central nerveous system. Objective: As a solution, the objective of this literature review is to identify the potency of CRISPR/Cas9 encapsulated by LPNs as a novel therapeutic strategy against HD. Method:The authors constructed this literature review by analizing and synthesizing 81 full text journal published no longer than 10 years ago that are relevant with the topic discussed in this literature review.Discussion: CRISPR/Cas9 is able to intervene the N-Terminal of the mutated HTT gene (mHTT) specifically this intervention results in attenuated expression of the mHTT significantly which hamper the expression of reactive astrocyte and prevent further aggregation of the mHTT, thus ameliorate the condition of HD’s patients. LPNs play as vector that deliver CRISPR/Cas9 in order to be able to get through the blood brain barrier. Having low toxicit yand immunogenecity, this vector could improve effectivity and efficiency of this novel therapeutic strategy.Conclusion : CRISPR/Cas9 encapsulated by LPNs could be a promising novel therapeutic strategy to treat HD efficiently, effectively, and safely.Keywords: CRISPR/CAS9, huntingtin, Huntington disease, LPNs, mHTT